Fast‐field‐cycling NMR at very low magnetic fields: water molecular dynamic biomarkers of glioma cell invasion and migration. (19th January 2022) - Petit, Manuel; Leclercq, Maxime; Pierre, Sandra; Ruggiero, Maria Rosaria; El Atifi, Michèle; Boutonnat, Jean; Fries, Pascal H.; Berger, François; Lahrech, Hana
Abstract : Our objective was to study NMR relaxometry of glioma invasion/migration at very low field (<2 mT) by fast‐field‐cycling NMR (FFC‐NMR) and to decipher the pathophysiological processes of glioma that are responsible for relaxation changes in order to open a new diagnostic method that can be extended to imaging. The phenotypes of two new glioma mouse models, Glio6 and Glio96, were characterized by T 2w ‐MRI, HE histology, Ki‐67 immunohistochemistry (IHC) and CXCR4 RT‐qPCR, and were compared with the U87 model. R 1 dispersions of glioma tissues were acquired at low field (0.1 mT‐0.8 T) ex vivo and were fitted with Lorentzian and power‐law models to extract FFC biomarkers related to the molecular dynamics of water. In order to decipher relaxation changes, three main invasion/migration pathophysiological processes were studied: hypoxia, H2 O2 function and the water‐channel aquaporin‐4 (AQP4). Glio6 and Glio96 were characterized with invasion/migration phenotype and U87 with high cell proliferation as a solid glioma. At very low field, invasion/migration versus proliferation was characterized by a decrease in the relaxation‐rate constant (Δ R 1  ≈ −32% at 0.1 mT) and correlation time (≈−40%). These decreases corroborated the AQP4‐IHC overexpression (Glio6/Glio96: +92%/+46%), suggesting rapid transcytolemmal water exchange, which was confirmed by the intracellular water‐lifetime τ IN decrease (Δ τ IN  ≈ −30%). In functional experiments, AQP4 expression, τ IN and the relaxation‐rate constant at very low field were all found to be sensitive to hypoxia and to H2 O2 stimuli. At very low field the role of water exchanges in relaxation modulation was confirmed, and for the first time it was linked to the glioma invasion/migration and to its main pathophysiological processes: hypoxia, H2 O2 redox signaling and AQP4 expression. The method appears appropriate to evaluate the effect of drugs that can target these pathophysiological mechanisms. Finally, FFC‐NMR operating at low field is demonstrated to be sensitive to invasion glioma phenotype and can be straightforwardly extended to FFC‐MRI as a new cancer invasion imaging method in the clinic. Abstract : FFC‐NMR relaxometry at very low field is demonstrated, discriminating glioma invasion/migration from proliferation. Changes were linked to the main glioma invasion/migration pathophysiologies: hypoxia, H2 O2 redox signaling and AQP4 functions, all acting on transcytolemmal water exchanges. It is an innovative theranostic method that can be extended to FFC‐MRI to evaluate drugs targeting invasion/migration processes.